The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1055/s-2006-925125
|View full text |Cite
|
Sign up to set email alerts
|

Meal-dependent Regulation of Circulating Glycated Insulin in Type 2 Diabetic Subjects

Abstract: There is mounting evidence that elevated circulating concentrations of glycated insulin play a role in insulin resistance in type 2 diabetes. This study evaluated the secretion of glycated insulin in response to enteral stimulation in type 2 diabetic subjects. Following a mixed meal (450 kcal; 44 % carbohydrate; 40 % fat; 16 % protein), glycated insulin rose 10-fold to peak (60 min) at 104.5 +/- 25.0 pmol/l (p < 0.001), representing 22 % total circulating insulin. The response paralleled early rises in insulin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Furthermore, there is clear evidence that glycation and AGEs lead to mitochondrial dysfunction [15,16] and impaired immune responses [17,18,19]. Glycation of growth factors such as platelet-derived growth factor (PDGF) [20] and insulin [21,22,23], as well as receptors such as nerve growth factor (NGF)-receptor [24], were reported to affect signaling functions.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, there is clear evidence that glycation and AGEs lead to mitochondrial dysfunction [15,16] and impaired immune responses [17,18,19]. Glycation of growth factors such as platelet-derived growth factor (PDGF) [20] and insulin [21,22,23], as well as receptors such as nerve growth factor (NGF)-receptor [24], were reported to affect signaling functions.…”
Section: Introductionmentioning
confidence: 99%
“…Following the transport of glucose into the pancreatic beta cell via Glut-2 glucose transporters, insulin is rapidly glycated during the stages of cellular insulin biosynthesis and storage. These glycated proteins have been identified in the pancreatic beta cell in animal and cellular models of diabetes [40][41][42][43] and recent human studies have confirmed the pancreatic beta cell as a highly favourable environment for glycation [44][45][46][47]. Increasing evidence supports a role for glycated insulin in the insulin resistant state of type 2 diabetes [48,49].…”
Section: Evaluation Of Glycaemic Status In Diabetesmentioning
confidence: 95%
“…Although the mechanisms of AGE-induced pancreatic β -cell dysfunction have to be further clarified, evidence indicates that AGEs interfere with several steps of the insulin-mediated regulation of glucose: AGEs inhibit the production of ATP needed for insulin secretion and decrease the expression of proteins involved in exocytosis of the insulin granules. Moreover, it has been demonstrated that glycation of insulin occurs during diabetes, and that glycated insulin represents a significant proportion of total circulating insulin in type 2 diabetes [82, 83]. Animal studies using isolated muscle and adipose tissue suggest that insulin glycation is associated with a significant compromise of its biological activity.…”
Section: Ages Activate Injury Pathways In Diabetic Pathophysiologymentioning
confidence: 99%